A) E(0,0) B) A(0,1) C) C(-1,0) D) D(0,-1)
A) FG=1 B) EA=1/2 C) EF=1 D) EG=1
A) x2-y2=1 B) x2+y2=1 C) x+y2=1 D) x2+y=1
A) 3 cm B) 4 cm C) 1 cm D) 2 cm
A) 2 cm B) 3 cm C) 1 cm D) 4 cm
A) (x+1)2+(y-1)2=(3)2 B) (x+1)2+(y+1)2=(3)2 C) (x+1)2+(y-1)2=(2)3 D) (x-1)2+(y-1)2=(3)2
A) x2+y2=1 B) x2-y2=1 C) x2+y2=-1 D) x2.y2=1
A) Reemplazar el valor de "x" en la ecuación x2+y2=1. B) Reemplazar el valor de "x" en la ecuación x2+y2=1 y despejar "y". C) Reemplazar el valor de "x" y despejar "y". D) Reemplazar el valor de "x" en la ecuación x2+y=1 y despejar "y".
A) cos30°=1/2 B) tan30°=1 C) sen30°=1/2 D) cot30°=1
A) cotα=1/co B) tanα=co/ca C) cosα=ca/h D) senα=co/h |